2020
DOI: 10.2147/jaa.s261441
|View full text |Cite
|
Sign up to set email alerts
|

<p>Longitudinal Association Between Diet Quality and Asthma Symptoms in Early Adult Life in a Brazilian Birth Cohort</p>

Abstract: Background: The role of diet in the etiology of asthma is still inconclusive. This paper evaluated the longitudinal association between diet quality and chest wheezing in young adults. Methods: This is a longitudinal study with follow-up information from 18-and 22-year-olds (18y and 22y) of the 1993 Pelotas (Brazil) Birth Cohort. Chest wheezing occurrence and number of events in the last year were reported at 22y. Diet quality was measured with a revised version of the Healthy Eating Index (IQD-R) for the Braz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…To our knowledge, five studies have investigated the association between the AHEI-2010 and asthma outcomes, among young [39] to middle-aged adults [17,18,40,41], and using a dichotomous [39][40][41] or a continuous [17,18] definition of asthma, and they reported mixed findings. The three studies that used a dichotomous definition of asthma, namely wheezing (yes/no), incident asthma (yes/no), or at Models were adjusted for age, energy intake, physical activity, smoking (excepted in models stratified by smoking status), educational level, marital status and having farmer parents.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, five studies have investigated the association between the AHEI-2010 and asthma outcomes, among young [39] to middle-aged adults [17,18,40,41], and using a dichotomous [39][40][41] or a continuous [17,18] definition of asthma, and they reported mixed findings. The three studies that used a dichotomous definition of asthma, namely wheezing (yes/no), incident asthma (yes/no), or at Models were adjusted for age, energy intake, physical activity, smoking (excepted in models stratified by smoking status), educational level, marital status and having farmer parents.…”
Section: Discussionmentioning
confidence: 99%
“…Although dietary scores are different, the discrepancies between the studies could rather be explained by the different populations (middle-aged men and women in the previous study vs. older women), as well as the difference in classification for the reference group. To our knowledge, six other studies investigated the association between different dietary scores (the AHEI-2010 [ 40 , 41 , 42 , 43 ], the Mediterranean diet score [ 43 ], or the Dietary Inflammatory Index (DII) [ 44 , 45 ]) and asthma outcomes among young [ 41 ] to middle-aged adults [ 40 , 41 , 42 , 43 , 44 , 45 ]. Studies using a dichotomous definition of asthma reported mostly inconclusive associations [ 40 , 41 , 42 , 44 , 45 ], whereas the study based on the continuous asthma symptoms score reported that a healthy diet (evaluated through the AHEI-2010 or the Mediterranean diet score) was associated with lower asthma symptoms [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, six other studies investigated the association between different dietary scores (the AHEI-2010 [ 40 , 41 , 42 , 43 ], the Mediterranean diet score [ 43 ], or the Dietary Inflammatory Index (DII) [ 44 , 45 ]) and asthma outcomes among young [ 41 ] to middle-aged adults [ 40 , 41 , 42 , 43 , 44 , 45 ]. Studies using a dichotomous definition of asthma reported mostly inconclusive associations [ 40 , 41 , 42 , 44 , 45 ], whereas the study based on the continuous asthma symptoms score reported that a healthy diet (evaluated through the AHEI-2010 or the Mediterranean diet score) was associated with lower asthma symptoms [ 43 ]. Differences in findings may result from the assessment of asthma (continuous or dichotomous), the assessment of diet (dietary scores based on recommended foods or nutrients for disease prevention or related to pathophysiological processes relevant to asthma), or the role of BMI in the association (confounder vs. mediator).…”
Section: Discussionmentioning
confidence: 99%
“…Lower values in the Revised Brazilian Healthy Eating Index score, representing lower dietary quality, both at 18 and 22 years old, increased the odds of wheezing in the previous year, with an OR = 1.97, 95% CI 1.33; 2.91, and OR = 1.98, 95% CI 1.36; 2.87, respectively, in a longitudinal study. On the other side, remaining on a poor diet from ages 18 to 22 increased the odds of chest wheezing by more than three-fold (OR = 3.28; 95% CI 1.84; 5.84) compared to staying on a high-quality diet [109].…”
Section: Dietary Patternsmentioning
confidence: 98%